2018
DOI: 10.1186/s13104-018-3617-x
|View full text |Cite
|
Sign up to set email alerts
|

Availability and sufficiency of phenobarbital, an essential medication, in Bhutan: a survey of global and neuropsychiatric relevance

Abstract: ObjectiveWe aimed to provide a reliable evidence-based conclusion around manufacturing, import, availability and sufficiency of one essential medication, phenobarbital (PB) through our example location (Bhutan). The relevant details about manufacturing, import, annual quantity, dose strength were obtained.ResultsThere was no local manufacturing of PB and all other anti-seizure medications. A total of 1068 vials of PB 200 mg/mL inj and 489,350 tablets of PB30 mg (i.e. 14.6 kilos) was estimated to annually becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Besides, all this, today, Islam is the fastest growing religion in the world and may sooner or later become the most prevalent. For instance, Islam grew 15.0% in the last five years in Australia; the Christians are reduced to 70.0% in Sweden; in 2008, 61.0% of those who annually migrated to France belonged to Meghreb [12] ; by 2040 the Islam would become the 2 nd largest religion in USA; in UK about 100,000 convert to Islam every year which showed a 12.0% growth in the last three years. It is also important to note that for MENA countries, like Algeria and Tunisia, having the nationality of their colonial country (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, all this, today, Islam is the fastest growing religion in the world and may sooner or later become the most prevalent. For instance, Islam grew 15.0% in the last five years in Australia; the Christians are reduced to 70.0% in Sweden; in 2008, 61.0% of those who annually migrated to France belonged to Meghreb [12] ; by 2040 the Islam would become the 2 nd largest religion in USA; in UK about 100,000 convert to Islam every year which showed a 12.0% growth in the last three years. It is also important to note that for MENA countries, like Algeria and Tunisia, having the nationality of their colonial country (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…17 Eight molecules of ASM (carbamazepine, phenobarbital, phenytoin, sodium valproate, diazepam, gabapentin, lamotrigine, and magnesium sulfate) are registered in the essential drug list of Cambodia (9th edition, 2018) which are provided free of charge in public healthcare facilities. 18 However, epilepsy has the highest number of treatment dropouts, more than any other neuropsychiatric disorder. 16 A study in Cambodia performed in 2012 has shown that only a third of PWE (34.3%) were treated by ASM, and a high proportion of patients (43%) were not on any treatment.…”
Section: Introductionmentioning
confidence: 99%